FINANCIAL HEALTH AND SMALL BUSINESS DEVELOPMENT IN CROSS RIVER STATE NIGERIA: DOES STRATEGIC INVENTORY MATTER? (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the nexus between strategic inventory management and the financial health of small businesses in Cross River State, Nigeria. Utilizing a cross-sectional survey design, primary data were collected from 300 small business owners across various sectors in Calabar Metropolis and other urban centers. The findings reveal a significant positive correlation between effective inventory management practices and financial performance, with businesses employing strategic inventory techniques reporting higher profitability and liquidity. Demographic analysis indicates that younger entrepreneurs and those with higher education levels are more likely to adopt advanced inventory practices. The study underscores the critical role of inventory optimization in mitigating financial distress and enhancing business sustainability in resource-constrained settings. Recommendations include targeted training programs on inventory management and policy support for small businesses to access affordable inventory management systems. These insights contribute to the discourse on small business development in developing economies, emphasizing the need for strategic operational practices to bolster financial resilience.